Spectral characteristics of the quasi-biennial oscillation of total Ozone (MAUSAM, 1999)
The 12-month running means of the 50 hPa low latitude zonal wind and total ozone values for the latitude zones NP (North Polar), NT (North Temperate), TRO (Tropical), ST (South Temperate), SP (South Polar) were subjected to special analysis, separately over the two successive 18 year intervals, 1958-1975 and 1976-1993. In the interval 1958-1975, the wind had a prominent peak at 2.45 years and two smaller but significant peaks at 1.98 and 3.05 years. For ozone only NP. NT and ST had roughly similar peaks (2.37, 2.41, 2.48 years), while TRO and SP had different peaks (2.27 and 2.12 years). All ozone series had significant peaks at 20-21 months, barely significant in the wind series. Ozone peaks were noticed in the 3-5 years band also. In the interval 1976-1993, the patterns were different. The wind had only one prominent peak at 2.51 years. For ozone, NP, NT, ST had roughly similar peaks (2.41, 2.45, 2.45 years) while TRO. Speed different peaks (2.32 and 2.29 years). All ozone series had significant peaks at 20-22 months and in the 3-5 year band; but these were absent in the wind series. The 3-5 year band probably indicates ENSO effects. A cross-correlation analysis between wind and ozone showed that TRO maxima coincided with westerly wind maxima. while NT, ST and NT, NP were phase shifted by 4 and 6 seasons.